2019
DOI: 10.1016/j.cegh.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Association between metabolic risk, oxidative stress and rotating shift work in a tertiary health care facility

Abstract: Healthcare industry employees, work in rotating shift duties to provide 24/7 services. Shift work is known to disrupt circadian rhythm and predispose the employees to metabolic risk and oxidative stress, subsequently increasing the risk for Non-Communicable Diseases. Present study attempts to evaluate this association. Aims: To evaluate the association between metabolic risk and oxidative stress among health care personnel working in rotating night-shift as compared to dayshift. Settings and design: Cross sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…The etiopathological mechanism of how shift work leads to AMD has not been identified, although previous studies have shown the association between shift work and oxidative stress [ 10 11 12 13 14 15 ], which is a known risk factor for AMD [ 28 29 30 31 ]. ROS are highly reactive molecules owing to their unpaired electrons, and ROS overproduction beyond an acceptable range of endogenous antioxidants is called oxidative stress [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The etiopathological mechanism of how shift work leads to AMD has not been identified, although previous studies have shown the association between shift work and oxidative stress [ 10 11 12 13 14 15 ], which is a known risk factor for AMD [ 28 29 30 31 ]. ROS are highly reactive molecules owing to their unpaired electrons, and ROS overproduction beyond an acceptable range of endogenous antioxidants is called oxidative stress [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, shift work is associated with chronic diseases such as cardiovascular diseases, diabetes mellitus (DM), metabolic syndrome, and breast cancer [ 9 ]. Recent studies have suggested that circadian rhythm changes can lead to oxidant-antioxidant imbalances and cause oxidative stress [ 10 11 12 13 14 15 ]. Sharifian et al [ 12 ] noted that total plasma antioxidant capacities were lower in night-shift workers and suggested that night shift work can act as an oxidative stressor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations in the circadian cycle commonly have physiological consequences, for example, the night work with sleep deprivation can decrease the melatonin levels and may be linked to cardiometabolic and body alterations. 8 9 10 Sleep deprivation is a loss of night's sleep 11 or when the total sleep time per night is not enough, sleep is considered shorter than need. On average, short sleep lasts less than 5 or 6 hours a day.…”
Section: Introductionmentioning
confidence: 99%
“…Irregular working hours can disturb sleep and lead to some psychological problems in the long run [ 8 ]. Besides, working in rotating time frame is known as a risk factor for metabolic syndrome, oxidative stress, and some of other non-communicable diseases risk factors [ 9 ]. Several studies on seafarers’ physical health status have revealed that the prevalence of these risk factors such as metabolic syndrome is high among seafarers [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%